2019
DOI: 10.1002/jrs.5631
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of amorphization in nanocrystalline 3C–SiC irradiated with C+ and He+ ions

Abstract: This study examines C+ and He+ ion irradiation‐induced amorphization processes in 3C–SiC nanograins embedded in an amorphous SiC matrix. Raman spectroscopy and Rutherford backscattering spectrometry are used for damage characterization. SiC grains with an average size of either ~6 or ~20 nm were observed to be fully amorphized to a lower dose at room temperature compared with their monocrystalline counterpart under the identical irradiation condition. In addition to damage accumulation‐induced amorphization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Due to the presence of GBs, the defects in the pre-existing disordered region continue to increase via atomic displacements, while the GBs also attract the growth and coalescence of clusters. It is similar to the results that preferential amorphization at the interfaces could play a significant role of amorphization [29]. The number of defects production is very close to constant above 0.55 dpa, suggesting that a NC-A transformation is highly accomplished.…”
Section: Resultssupporting
confidence: 88%
“…Due to the presence of GBs, the defects in the pre-existing disordered region continue to increase via atomic displacements, while the GBs also attract the growth and coalescence of clusters. It is similar to the results that preferential amorphization at the interfaces could play a significant role of amorphization [29]. The number of defects production is very close to constant above 0.55 dpa, suggesting that a NC-A transformation is highly accomplished.…”
Section: Resultssupporting
confidence: 88%
“…Their results were discussed in terms of possible applications of Raman for express‐diagnostics of doped Si nanostructures for photonics and thermoelectronic applications. Zhang et al [ 101 ] reported a Raman study of amorphization in nanocrystalline 3C–SiC irradiated with C+ and He+ ions. Their results may have important implications for nanocrystalline SiC to be applied in advanced nuclear reactors.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…In this extent, Raman spectroscopy offers more cost-friendliness and accessibility. This second technique is also widely used for damage and amorphization characterization after ion implantation [7]- [12]. Particularly, a disordered material will allow more degrees of freedom to its atoms due to the presence of vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the Raman response of a bi-atomic compound such as SiC will reflect the disorder through the apparition of broad bands, characteristic of the Raman-active Si-Si, Si-C or C-C disordered phonons. The amplitude of those can then be used to quantify the crystallinity of the material when compared to a pristine reference [7], [12]. Raman spectroscopy may as well come in useful for doping characterization in polar semiconductors such as InP or GaN or SiC [5], [6].…”
Section: Introductionmentioning
confidence: 99%